Blended Learning in English Language Teaching Contexts - Mohammed, Amal (DIRASAT: EDUCATIONAL SCIENCES, 2018)
The use of Blended Learning in English language teaching (ELT) contexts has increased significantly during the past decade .The present study reveals an overview of Blended Learning in ELT by considering where the term originated and by seeking to define what it means. This study also demonstrates an overview of Blended Learning through relevant literature and the current studies on Blended Learning in ELT contexts. Different blends and strategies used in implementing Blended Learning in ELT contexts are presented. Literature survey in recent study reveals that Blended Learning is more favorable than pure face-to-face or online instruction and offers advantages of Blended learning approach over them. Besides, the researcher demonstrates an overview of the limitations of the Blended Learning approach in ELT. Finally, the researcher concludes that Blended Learning might be an efficient instructing approach and recommends conducting further research on teachers’ required skills for using Blended Learning in ELT contexts.